Hermeneutical Approach in Understanding Intercultural Communication - Varsonova D. A. (Psychology of Personal Interaction in Modern Society, 2022)
A hermeneutic approach is used to solve the problems connected with interpretation of speech units and construction of intercultural and interpersonal relations. The dialogue of cultures should be based on the understanding of the addressee and the addressee of their distinctive features, as well as the mutual process of learning different features of their cultures. The article provides a definition of the concept of «hermeneutics», aspects to its understanding, the problems of understanding the expression and cultural identity are considered.
Keywords: интерпретация; диалог; коммуникация; dialogue; понимание; герменевтика; communication; interpretation; understanding; hermeneutical